1977
DOI: 10.1039/p19770002462
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations. Part 11. Photorearrangement of 1-(2-pyridyl)- and 1-(3-pyridyl)-2-nitropropenes

Abstract: bury, Kent CT2 7NHPyrex-filtered irradiation of 1 -(2-pyridy1)-and 1 -(3-pyridyl)-2-nitropropene in acetone solution gives 1 -(2-pyridyl)and 1 -(3-pyridyl) -1 -hydroxyiminopropan-2-one, respectively, in high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…1. The structure of (2a) was postulated by analogy to the photorearrangement of several a$-unsaturated nitroalkanes (Chapman et al, 1966; Hunt andReid, 1972, 1977), while that of (3a) derived from the observed oxadiazole formation (Clapp, 1976). Pfoertner and Daly (1987) recently confirmed the formation of 5-methyl-1,2,4-oxadiazole-3-carboxamides as the ultimate product of the photochemical rearrangement of 2-methyl-5-nitroimidazoles but failed to isolate the iminoketone intermediate in a state sufficiently pure to enable adequate spectral data to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…1. The structure of (2a) was postulated by analogy to the photorearrangement of several a$-unsaturated nitroalkanes (Chapman et al, 1966; Hunt andReid, 1972, 1977), while that of (3a) derived from the observed oxadiazole formation (Clapp, 1976). Pfoertner and Daly (1987) recently confirmed the formation of 5-methyl-1,2,4-oxadiazole-3-carboxamides as the ultimate product of the photochemical rearrangement of 2-methyl-5-nitroimidazoles but failed to isolate the iminoketone intermediate in a state sufficiently pure to enable adequate spectral data to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This material could be prepared in a manner similar to 1 . A previous report described a two-step photochemical route which afforded oxime 6 in 12% yield . We prepare this same species in 65% yield from pyrid-2-yl acetone 7 by treatment with sodium nitrite in sulfuric acid.…”
mentioning
confidence: 99%